Intraocular surgery : a basic surgical guide - Williamson, Thomas H. (Springer, 2016)
This book instructs postgraduate trainees in ophthalmology on the basic methodology required to perform intraocular surgery. The text is written clearly and concisely, investigating basic surgical skills for the eye to facilitate the training process. The subject material of each chapter has been carefully chosen to explain separate conceptual areas in surgery to allow easy understanding and rapid attainment of knowledge. The concepts can be transferred from one surgical method to another, giving the reader the flexibility to adapt to new methods quickly. Intraocular Surgery - A Basic Surgical Guide provides various insights to allow the development of a thoughtful and considered approach to surgery. It encourages the reader to more intelligently scrutinize which surgical methods to apply, and to utilize the most effective procedures in clinical practice. After reading this book, the reader will be well-equipped to perform the simple steps of surgery, improving the overall quality of surgery.